The London position statement of the World Congress of Gastroenterology on Biological Therapy for IBD with the European Crohn's and Colitis Organisation: safety. - Van Assche, G; Lewis, J; Lichtenstein, G; Loftus, E; Ouyang, Q; Panes, J; Siegel, C; Sandborn, W; Travis, S; Colombel, J (2011)
This paper in the series from the World Congress of Gastroenterology addresses the safety and immunogenicity of biological therapy. The safety profile in randomized controlled studies of all biological agents in Crohn's disease (CD) and ulcerative colitis has been generally favorable, but a small percentage of patients experience severe side effects on biological therapy, including pneumonia, tuberculosis, lymphoma, demyelination, drug-induced lupus, or hepatotoxicity. Although there is unequivocal evidence of an increased risk of serious infection among patients with rheumatoid arthritis treated with anti-tumor necrosis factor therapy, the evidence is less clear in CD. The risk of infection may be increased by combination therapy with steroids and/or immunomodulators. There is a specific risk of the rare γ δ hepatosplenic lymphoma that appears to have a predeliction for young males on combination therapy. The α4 integrin antagonist natalizumab also carries a specific risk of progressive multifocal leucoencephalopathy and reactivation of JC virus infection. The immunogenicity of biological therapy is complex: all agents are potentially immunogenic and this can be reduced by combination with immunomodulators. This may enhance both therapeutic efficacy and the risk of infection or malignancy, so the balance of risk and benefit must be judged for individual patients.